Current evidence for a strategic approach to the management of rheumatoid arthritis with disease-modifying antirheumatic drugs: a systematic literature review informing the EULAR recommendations for the management of rheumatoid arthritis. Issue 6 (6th May 2010) - Knevel, R; Schoels, M; Huizinga, T W J; Aletaha, D; Burmester, G R; Combe, B; Landewé, R B; Smolen, J S; Sokka, T; van der Heijde, D M F M
Abstract : Objectives: To perform a systematic literature review of effective strategies for the treatment of rheumatoid arthritis (RA). Methods: As part of a European League Against Rheumatism (EULAR) Task Force investigation, a literature search was carried out from January 1962 until February 2009 in PubMed/Ovid Embase/Cochrane and EULAR/American College of Rheumatism (ACR)) abstracts (2007/2008) for studies with a treatment strategy adjusted to target a predefined outcome. Articles were systematically reviewed and clinical outcome, physical function and structural damage were compared between intensive and less intensive strategies. The results were evaluated by an expert panel to consolidate evidence on treatment strategies in RA. Results: The search identified two different kinds of treatment strategies: strategies in which the reason for treatment adjustment differed between the study arms ('steering strategies', n=13) and strategies in which all trial arms used the same clinical outcome to adjust treatment with different pharmacological treatments ('medication strategies', n=7). Both intensive steering strategies and intensive medication strategies resulted in better outcome than less intensive strategies in patients with early active RA. Conclusion: Intensive steering strategies and intensive medication strategies produce a better clinical outcome, improved physical function and less structural damage than conventional steering or treatment. Proof in favour of any steering method is lacking and the best medication sequence is still not known.